Gravity and trade in video on demand services - Annette Broocks; Zuzanna Studnicka (European Commission, Joint Research Centre (JRC), 2021)
Over the last decade, watching videos online has become one of the primary uses of the internet, with streaming services accounting for more than 60% of global internet traffic. In this paper we use a novel data set on Netflix, the largest streaming platform worldwide, to estimate the patterns of catalogue availability (extensive margin) and number of clicks per title (intensive margin) across twenty countries. This data set also gives us a unique opportunity to estimate the importance of quality in viewing patterns. Our results show evidence of the gravity framework explaining both margins of Netflix watching. In addition, we find that there is a strong preference for domestic content, better-rated titles, and Netflix Original productions. These findings suggest that as Netflix produces more content, this will interact with its streaming dominance to provide a significant advantage in reaching viewers and promoting specific content.
Keywords: F10; L82; Z10; 330; Netflix; subscription video on demand; gravity equation; services trade